Influence of surface modification to stainless steel on initial Streptococcus mutans adhesion and antibacterial acivity - Nurhaerani, Nurhaerani; Oewen, Roosje Rosita; Herdiyati, Yetty (Universitas Padjadjaran, 2010)
Introduction: Stainless steel is one of the most frequently used material in pediatric dental clinic for stainless steel crown, bracket, molar band and archwire. The purposes of this study were to evaluate the surface characteristic (chemichal composition, hydrophobicity, fluoride release), antibacterial activity of modified stainless steel and to evaluate the initial adhesion S. mutans on the surface of modified stainless steel. Methods: This study was an experimental laboratory. Sample used in this study was Stainless steel which modified with the plasma based fluorine ion implantation. The stainless steel which was fluorine ion implanted by CF4 gas was washed in a ultrasonic bath containing distilled water for 10 minute. The modified stainless steel materials were washed in an ultrasonic bath containing distilled water for 10 minute. Stainless steel material was incubated at 37°C in 2 ml of BHI broth containing S. mutans with concentration 2x107 CFU/ml. After 48 hours incubation, a 0.5 ml of solution was immediately transferred into 4.5 ml of PBS (-) and diluted. A 100 pi of diluted solution was plated on BHI agar. After 48 hours culture at 37°C, the number of colonies was counted. The numbers of fluorine ion implanted material and fluorine ion non-implanted control were ten, respectively. Results: XPS analysis showed the presence of fluorine and chromic fluoride until second layer. The contact angle of modified stainless steel was significantly increased A small amount of fluorine ion released from surface of modified stainless steel was detected until the second day. Fluorine ion implanted of stainless steel was significantly decreased the initial adhesion and increased the antibacterial activity. Conclusion: The adhesion of S. mutans on the surface of stainless steel for 4 hours incubation is shown in Figure 11. Fluorine ion implanted stainless steel showed less bacterial adhesion than fluorine ion non- implanted control (p<0.001).